When Blogging Meets News Writing: Indonesian EFL Student Teachers’ Experiences in a Journalism Course - Dwi Sloria Suharti; Syaadiah Arifin; Diah Aryani; Hani Dewi Ariessanti (International Journal of Educational Research, 2026)
This study explores Indonesian EFL student teachers’ experiences of learning to write news articles through blogging in a Journalism course. The study was motivated by the need to provide meaningful and genre-based writing practice for EFL student teachers, who often face difficulties in generating ideas, organizing information, meeting genre expectations, and writing for authentic aences. Employing a qualitative case study design, the study involved twenty undergraduate student teachers from a private Islamic university in Tangerang, Indonesia; all participants completed an online quetaire, and five volunteers joined follow-up semi-structured interviews. The questionnaire data were alysed descriptively, while the interview data were examined thematically. The findings indicate that blogging supported regular writing practice, helped students understand news text structure, enouraged clearer organization of headlines, leads, and supporting details, and increased engagement by allowing students to publish and share their work. Blogging also promoted peer interaction and selfevaluation because students could read, compare, and comment on one another’s posts. However, some paticpants eprienced challenges related to technical blogging skills, uncertainty about writing standards, limited peer feedback, and discomfort with public online publication. The study concludes that blogging can serve as a useful platform for EFL news writing when it is supported by explicit istrucion, relevant tasks, clear assessment criteria, structured feedback, and ethical awareness in using digital and AI-driven tools.